The Dynamics of Decentralisation Policy in Indonesia from 1999 to 2025: A Scoping Review Approach - Ardika Nurfurkon (Fakultas Politik Pemerintahan IPDN, 2025)
Abstract This study aims to explore the dynamics of decentralisation policy between 1999 and 2025 in Indonesia using a scoping review, thereby providing an important historical record for the implementation of decentralisation policy in Indonesia. This study also strengthens the literature and trends regarding the dynamics of decentralisation policy in Indonesia and identifies issues concerning the dynamics of decentralisation policy in Indonesia. The research method used is a literature study with a scoping review approach. Scoping review is relevant in presenting a comprehensive map of research findings related to the dynamics, realities, and problems in the dynamics of decentralisation policy in Indonesia, while also identifying research gaps that still need to be explored. Data collection was carried out from the scopus.com website on decentralisation policy in Indonesia from 861 studies that were scoped down to 20 studies for analysis. The results of the study show that there are five themes related to decentralisation policy in Indonesia, namely local governance and accountability, decentralisation policy in education, natural resource and environmental management, public services and health, and fiscal decentralisation and corruption. This study contributes to the development of literature on decentralisation policy in Indonesia and has implications for the development of public policy and governance studies. Keywords: Decentralisation Policy, Governance, Scoping Review.